The use of long-acting drugs for the treatment of periodontitis - Sulym, Ю. В.; Petryshyn, О. А. (Actual Dentistry, 2021)
Resume. The most common and universal method of treating periodontitis is periodontal pocket curettage and root surface smoothing (SRP), after which it is important to prevent re-infection of the pocket. For this purpose, antibiotics and other antimicrobial drugs are prescribed. For many years, periodontists have used the systemic administration of high doses of antibiotics during and after the completion of SRP in order to achieve the desired concentration of the drug in the gingival fluid. Such tactics often led to organic complications. In recent years, the method of introducing antimicrobial agents immobilized on natural or synthetic polymers directly into the periodontal pocket has become widespread. Such compositions slowly dissolve on the spot and eventually release the desired drug component. The study analyzes the publications of recent years on the use of controlled release systems of drugs injected into the periodontal pocket. The most common problems that may arise during the application of this method of treatment are analyzed. The advantages and disadvantages of using such systems are indicated. The indications and contraindications for the use of controlled drug delivery systems are considered, data on their comparative clinical efficacy are given. The main dosage forms used for introduction into the periodontal pocket are described, the drugs registered and sold in Ukraine are listed and the data on their therapeutic efficacy. The future prospects of application of this method in periodontology are also considered in the work.